Formate auxotroph of Methanobacterium thermoautotrophicum Marburg. - Tanner, R S (1989)
A formate-requiring auxotroph of Methanobacterium thermoautotrophicum Marburg was isolated after hydroxylamine mutagenesis and bacitracin selection. The requirement for formate is unique and specific; combined pools of other volatile fatty acids, amino acids, vitamins, and nitrogen bases did not substitute for formate. Compared with those of the wild type, cell extracts of the formate auxotroph were deficient in formate dehydrogenase activity, but cells of all of the strains examined catalyzed a formate-carbon dioxide exchange activity. All of the strains examined took up a small amount (200 to 260 mumol/liter) of formate (3 mM) added to medium. The results of the study of this novel auxotroph indicate a role for formate in biosynthetic reactions in this methanogen. Moreover, because methanogenesis from H2-CO2 is not impaired in the mutant, free formate is not an intermediate in the reduction of CO2 to CH4.